2014
DOI: 10.5742/mejb.2014.92382
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emiratisation on Job Description Issues

Abstract: Job description plays a key role when hiring or applying for any job at any organization. It details the job to be performed, and roles and responsibilities involved clearly so as to clarify the applicant with his work. There are many associated issues with job description in the current industrialised world as employees who are not very well clear of their job description are just made to perform any task that is highly critical. This activity is leading to major failures and losses in the business to lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The UAE's policy of Emiratisation has both helped reduce the unemployment rate of Emirati graduates (Daleure, 2016) and created job frustration and tense workplace environments (Alabdelkarim et al, 2014), as Emiratis are promoted and overcompensated without sufficient qualifications or experience (Kirk, 2010). The national prioritisation of work in the public sector indicates a lack of readiness to meet the challenges of a knowledge-based economy.…”
Section: Attitude Towards Employmentmentioning
confidence: 99%
“…The UAE's policy of Emiratisation has both helped reduce the unemployment rate of Emirati graduates (Daleure, 2016) and created job frustration and tense workplace environments (Alabdelkarim et al, 2014), as Emiratis are promoted and overcompensated without sufficient qualifications or experience (Kirk, 2010). The national prioritisation of work in the public sector indicates a lack of readiness to meet the challenges of a knowledge-based economy.…”
Section: Attitude Towards Employmentmentioning
confidence: 99%
“…In addition, they believe that AA has not influenced levels of employment significantly, as unemployment remains too high within the GCC. Furthermore, Alabdelkarim et al (2014) found that in the Emirates, AA (Emiratisation) has made only a marginal contribution to overall job creation. In some sectors, it has actually led to job dissatisfaction and disruption of the work environment.…”
Section: Affirmative Action a In Relation To Employmentmentioning
confidence: 99%